The privacy of imagined groups and their impact on the technology of creating and managing digital content in public relations - NAWFEL, BENKHELIFA (Journal of Ecohumanism, 2026)
This study is intellectually grounded in the importance of understanding the specificity of imagined communities, represented by an institution’s various audiences—both current and prospective. It also examines the role of digital public relations in identifying and analyzing this specificity in order to manage relationships with target audiences on the one hand, and with public opinion on the other. The significance of this role is amplified within the internet environment, where digital public relations can transcend geographical boundaries. The internet functions as a rich medium that provides opportunities for information dissemination and persuasion, enables the delivery of richer content, supports consensus-building with diverse stakeholders, and facilitates interactive dialogue with broad and heterogeneous audience groups.From a methodological perspective, this study adopts an analytical approach by reviewing a set of foreign and Arab studies related to digital (electronic) public relations within the internet environment in general, and social media platforms in particular.In this context, public relations is expected to leverage the internet in managing and producing content through various digital applications and technologies, as well as through the continuous monitoring of users’ comments and tweets related to the organization’s activities in order to enhance its communication performance. This includes enabling audiences to better understand the organization, responding to their inquiries, addressing their concerns, providing access to important links to the official website and related platforms, and conducting digital research and surveys to meet audience needs. Such practices influence public perception, thereby impacting the organization’s reputation and strengthening trust in it.Accordingly, this study also seeks to examine public relations from a technical perspective by introducing the latest digital applications and software that assist public relations practitioners in managing and producing digital content within the specificities of the digital environment.